2019
DOI: 10.15823/p.2019.133.5
|View full text |Cite
|
Sign up to set email alerts
|

Mokytojų patirtys įgyvendinant ugdymo turinį: mokytojas, kaip švietimo politikos dalyvis, mokyklos bendruomenės narys ir profesionalas

Abstract: Straipsnyje analizuojama, kaip Lietuvos bendrojo ugdymo mokyklų mokytojai įgyvendina ugdymo turinį. Šis procesas apibūdinamas kaip kasdienis vyksmas, orientuotas į mokytojų galias konkrečiam ugdymo turiniui plėtoti, realizuoti ir įprasminti nuolatinėje ugdymo praktikoje. Fenomenografiniu tyrimu, kuriame dalyvavo 86 įvairių mokomųjų dalykų ir pradinio ugdymo mokytojai, nustatyta, kad ugdymo turinio įgyvendinimą mokytojas suvokia ir patiria kaip švietimo politikos dalyvis, mokyklos bendruomenės narys ir kaip pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…These people make independent decisions and choices in the working situation, easily conflict with the development of the school, and feel that their behavior is affected by the school. This is because a small number of teachers are immersed in independent work, ignoring the development of schools and education policies, and cannot have a positive impact on the overall school system [39]. Interestingly, when comparing groups of teachers with different teaching seniority, it was found that there were differences in the expression of teachers' psychological empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…These people make independent decisions and choices in the working situation, easily conflict with the development of the school, and feel that their behavior is affected by the school. This is because a small number of teachers are immersed in independent work, ignoring the development of schools and education policies, and cannot have a positive impact on the overall school system [39]. Interestingly, when comparing groups of teachers with different teaching seniority, it was found that there were differences in the expression of teachers' psychological empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Be abejonės, tokių mokytojų yra ir Lietuvoje. Tačiau mokytojų apklausos rodo, kad paprastai mūsų mokytojai nedalyvauja švietimo politikoje: "....tyrime dalyvavę mokytojai dažniau linkę užimti pasyvumo arba atsitraukimo poziciją nei imtis lyderystės, diskutuojant ar inicijuojant ugdymo turinio kaitą, atpažinus deklaruojamo ugdymo turinio silpnybes ar susidūrus su kliūtimis ugdymo praktikoje" [13].…”
Section: ˛Vadasunclassified